2008
DOI: 10.1167/8.14.25
|View full text |Cite
|
Sign up to set email alerts
|

The role of peripheral vision in saccade planning: Learning from people with tunnel vision

Abstract: Both visually salient and top-down information are important in eye movement control, but their relative roles in the planning of daily saccades are unclear. We investigated the effect of peripheral vision loss on saccadic behaviors in patients with tunnel vision (visual field diameters 7°–16°) in visual search and real-world walking experiments. The patients made up to two saccades per second to their pre-saccadic blind areas, about half of which had no overlap between the post- and pre-saccadic views. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 37 publications
(43 reference statements)
7
59
0
1
Order By: Relevance
“…In contrast, Crabb et al 7 found that patients with glaucoma made more saccades, fixations, and smooth pursuit eye movements per second than did controls, and the mean fixation duration was shorter. Luo et al 18 reported that patients with peripheral field loss and age-matched controls executed similar eye movements when performing visual search and real-world walking experiments. Natural tasks involving execution of actions differ from visual search tasks on static small images.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Crabb et al 7 found that patients with glaucoma made more saccades, fixations, and smooth pursuit eye movements per second than did controls, and the mean fixation duration was shorter. Luo et al 18 reported that patients with peripheral field loss and age-matched controls executed similar eye movements when performing visual search and real-world walking experiments. Natural tasks involving execution of actions differ from visual search tasks on static small images.…”
Section: Discussionmentioning
confidence: 99%
“…It is perhaps more surprising, though, that performance should diminish in the moving window condition when only peripheral vision was removed. It is frequently suggested that less-skilled observers experience perceptual narrowing in demanding situations with which they may not be familiar (eg Luo et al 2008;Weltman and Egstrom 1966); as a result, the less-skilled participants may have been expected to rely primarily on central vision. Our findings show that this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…We expected skilled basketball players to perform better than lesser-skilled players irrespective of the viewing condition, reflecting a superior ability to use both central and peripheral vision to support context-specific decision making. In contrast, because less-skilled observers are frequently found to experience perceptual narrowing in unfamiliar, demanding situations (eg Luo et al 2008;Weltman and Egstrom 1966), we expected the decision making of the less-skilled participants to be almost wholly supported by central vision. More specifically, we expected their performance to decrease in the moving mask condition when central vision was removed, but to remain unchanged in the moving window condition when only peripheral vision was removed and central vision was preserved.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This mechanism is similar to patients with peripheral visual loss that saccade to the blind area. 14 We therefore needed to verify that the brain can accurately spatiotopically map the retinotopic artificial vision from the electrical stimulation and that we have a method to calibrate eye trackers for the blind.…”
mentioning
confidence: 99%